Responsabilidad penal cometida con el uso de la inteligencia artificial y sistemas autónomos en delitos informáticos - Ganzhi Espinoza, Kleber Oswaldo (2025)
In the last decades, the artificial intelligence development and autouomous systems has highly advanced, it is so that currently human being is using it in different applications for their benefit, but also it has a negative side, that is for unscrupulous people use it in the commission of computer crimes, since it is a controversia! issue, for which is set the general objective to determine the criminal responsibility committed with the use of artificial intelligence and autonomous systerns in computer crimes, in Cañar province, in the year 2023; Facts that evidently generates serious violations of the fundamental rights of the victims and the society in general. The present research is qualitative, documentary type, the information has been obtained frorn scienrific articles, indexed magazines, interviews, inclusion and exclusion criteria publications that study the topic since different perspectives, which has allowed to carry out a holistic analysis, considering the origin, evolution and regulation of the topic under study. lt was shown that it is very difficult to determine with certainty the criminal responsibility in computer crimes, since autonomous systerns and artificial intelligence are increasingly more advanced, making difficult a certain investigatíon; added to that, the precarious technological infrastructure that the respective institutions have as well as the local and national level. lt is required an interrelated and joint work ata national and 'intemational level, with stable and compatible regulations to guarantee effective judicial protection, legal security and avoid impunity.